Are we justified in suggesting change to caffeine, alcohol, and carbonated drink intake in lower urinary tract disease? Report from the ICI‐RS 2015. Issue 4 (April 2017) - Robinson, Dudley; Hanna‐Mitchell, Ann; Rantell, Angie; Thiagamoorthy, Gans; Cardozo, Linda
Abstract : AIMS: There is increasing evidence that diet may have a significant role in the development of lower urinary tract symptoms. While fluid intake is known to affect lower urinary tract function the effects of alcohol, caffeine, carbonated drinks, and artificial sweeteners are less well understood and evidence from epidemiological studies is mixed and sometimes contradictory. The aim of this paper is to appraise the available evidence on the effect of caffeine, alcohol, and carbonated drinks on lower urinary tract function and dysfunction in addition to suggesting proposals for further research. METHODS: Literature review based on a systematic search strategy using the terms "fluid intake, " "caffeine, " "alcohol, " "carbonated" and "urinary incontinence, " "detrusor overactivity, " "Overactive Bladder, " "OAB." RESULTS: In addition to fluid intake, there is some evidence to support a role of caffeine, alcohol, and carbonated beverages in the pathogenesis of OAB and lower urinary tract dysfunction. Although some findings are contradictory, others clearly show an association between the ingestion of caffeine, carbonated drinks, and alcohol with symptom severity. CONCLUSIONS Given the available evidence lifestyle interventions and fluid modification may have an important role in the primary prevention of lower urinary tract symptoms. However, more research is needed to determine the precise role of caffeine, carbonated drinks, and alcohol in the pathogenesis and management of these symptoms. The purpose of this paper is to stimulate that research. Neurourol. Urodynam. 36:876–881, 2017 . © 2017 Wiley Periodicals, Inc.